2015
DOI: 10.1038/nature14402
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin enables maternal behaviour by balancing cortical inhibition

Abstract: Oxytocin is important for social interactions and maternal behavior. However, little is known about when, where, and how oxytocin modulates neural circuits to improve social cognition. Here we show how oxytocin enables pup retrieval behavior in female mice by enhancing auditory cortical pup call responses. Retrieval behavior required left but not right auditory cortex, was accelerated by oxytocin in left auditory cortex, and oxytocin receptors were preferentially expressed in left auditory cortex. Neural respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
747
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 636 publications
(780 citation statements)
references
References 56 publications
(86 reference statements)
28
747
3
2
Order By: Relevance
“…Indeed, OT has been shown to increase spike output [89][90][91] and facilitate synaptic long-term potentiation [92][93][94] and our data suggest an intrinsic mechanism that may underlie shifts in synaptic efficacy and excitatory/inhibitory balance found in brain regions where OT is critical for myriad social behaviors 67,74,90,95 . Intrinsic properties are shaped by ion channels.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Indeed, OT has been shown to increase spike output [89][90][91] and facilitate synaptic long-term potentiation [92][93][94] and our data suggest an intrinsic mechanism that may underlie shifts in synaptic efficacy and excitatory/inhibitory balance found in brain regions where OT is critical for myriad social behaviors 67,74,90,95 . Intrinsic properties are shaped by ion channels.…”
Section: Discussionmentioning
confidence: 92%
“…Given the dense expression of OTR in the insula and evidence that OT can modulate excitatory balance in cortical circuits 67 , we hypothesized that OT released during the SAP test could directly modulate insular cortex excitability. The excitability of insular cortex was characterized after bath application of OT (500nM) in whole-cell pyramidal neuron recordings ( Fig.…”
Section: Oxytocin Alters the Excitability Of The Insular Cortexmentioning
confidence: 99%
“…It has previously been shown that female mice with maternal experience display higher signal to noise ratios in their neural responses to pup cries than virgin females within this region (Liu et al, 2006;Rothschild et al, 2013). Marlin et al (2015) demonstrated that when housed with an experienced dam and her pups, virgin female mice receiving either systemic injections of oxytocin or optogenetic stimulation within the PVN started retrieving pups significantly earlier than saline treated virgins who required at least 2 days of co-housing before they expressed retrieval behaviour. In fact, systemic or central release of oxytocin triggered retrieval in virgin dams even without cohousing.…”
Section: Oxytocin Enhances the Salience Of Socially Relevant Sensorymentioning
confidence: 99%
“…A recent study by Marlin et al (2015) demonstrated that the acquisition of pup retrieval behaviour by female mice is dependent on the modulatory actions of oxytocin within auditory cortex. It has previously been shown that female mice with maternal experience display higher signal to noise ratios in their neural responses to pup cries than virgin females within this region (Liu et al, 2006;Rothschild et al, 2013).…”
Section: Oxytocin Enhances the Salience Of Socially Relevant Sensorymentioning
confidence: 99%
“…Then, as the oxytocin kicked in, the signal evolved into a more orderly pattern typical of a maternal brain. The study showed in unusual detail how the hormone changed the behaviour of neurons 1 . "Oxytocin is helping to transform the brain, to make it respond to those pup calls, " Froemke says.…”
mentioning
confidence: 99%